The Yield, Chemical Composition, and Antioxidant Activities of Essential Oils from Different Plant Parts of the Wild and Cultivated Oregano (Origanum vulgare L.) - Zoran Ilić; Ljiljana Stanojević; Lidija Milenković; Ljubomir Šunić; Aleksandra Milenković; Jelena Stanojević; Dragan Cvetković (Horticulturae, 2022)
The present study focuses on the yield, chemical composition, and antioxidant activity of essential oils from different parts (flowers or leaves/stems) of cultivated plants grown under pearl shade nets with a 40% shaded index or in nonshaded plants and wild-grown oregano. The chemical composition of isolated essential oils was determined by GC/MS and GC/FID. Antioxidant activity was determined using the DPPH assay. The highest yield of oregano essential oils (OEOs) was obtained in cultivated shaded plants (flowers) at 0.35 mL/100 g p.m., in contrast to nonshaded plants (flowers), where the yield of OEOs was low (0.21 mL/100 g p.m.). Qualitative and quantitative analyses of the OEOs identified 16–52 constituents that varied with origin and plant organs. The oxygenated sesquiterpene caryophylleneoxide (7.4–49.9%) was predominant in all the essential oil samples. Other major constituents were sesquiterpene hydrocarbon-germacrene D (8.4–22.5%) and (E)-caryophyllene (8.5–10.8%), monoterpene hydrocarbon-sabinene (1.6–7.7%), and oxygen-containing monoterpenes-terpinen-4-ol (1.5–7.0%). The plant part has a significant effect on the antioxidant activity of OEOs, while the influenceof modified light under the shade nets is significantly lower. The OEOs from wild flowers showed the highest antioxidant activity, with an EC50 value of 4.78 mg/mL. OEOs from cultivated nonshaded plants (flowers) recorded the lowest antioxidant activity with an EC50 value of 24.63 mg/mL. The results suggest that the yield and quality of OEOs can be scaled-up by optimizing plant production in comparison with wild-growing plants. The content and quality of OEO can be increased by optimizing its production compared to plants from the spontaneous flora. Adequate cultivation techniques, such as shading, can achieve high-quality oregano yields and better quality parameters in terms of specific OEO components and meet the different requirements of the market and industrial sectors.